Dinamika pertemanan sebagai variabel penentu motivasi prestasi: studi pada ukm taekwondo uin maulana malik ibrahim malang - Maulidiyah, Zahrotul Ani (Maliki Interdisciplinary Journal, 2026)
This study investigates the role of friendship dynamics in facilitating achievement motivation among members of the Taekwondo Student Activity Unit at UIN Maulana Malik Ibrahim Malang. Employing a qualitative descriptive design, data were obtained through in-depth interviews with five purposively selected informants. Thematic analysis was utilized to identify salient patterns of social interaction. The findings indicate that friendship relations characterized by warmth, group cohesion, and consistent peer support substantially contribute to the enhancement of achievement motivation. This influence operates through three primary mechanisms: (1) the establishment of psychological safety that increases training comfort, (2) the internalization of emotional and instrumental support that strengthens discipline, and (3) the reinforcement of training commitment moderated by emotional closeness among members. These results underscore the relevance of social support and group dynamics theories within the context of collegiate athletic performance.